Literary Parodies, Mockery, and Imitation as a Phenomenon of Different Voices in a Text - Shor, Julija V. (Respectus Philologicus, 2003)
In the present paper a parody is regarded as a phenomenon of merging different voices in a text where polyphony is formed due to the combination of author, translator and parodist’s voices. Using historic and literary methods of investigation along with the comparative method, some attempts were made to reveal the reasons of comic impression and to determine cultural and historic motives of a parody creation, with special attention being paid to the late 60-ies of the 20th century, the period of "detente" in art and literature in the former USSR. Parodies of various types are being analyzed: literary parody on the Soviet novel belonging to the period of Socialist Realism, parodies on translations in verse, imitations and different genre combinations, such as a mixture of poetic lines written by different poets, or singing poems to the music composed for other pieces of poetry.